Método de construção da escada da sustentabilidade: uma proposta metodológica para o estado do Ceará - Abreu, Lucas Araújo (2019)
It is very important to elaborate new proposals that take the form of support instruments to evaluate the sustainability level of the territories for analysis of existing human and environmental conditions. In Ceará, little has been done about it. In this context, the purpose of this study is to determine the situation presented by the state and its 184 municipalities in terms of sustainable development, using the Sustainability Ladder index. The ES construction was based on a methodological and applicable proposal and It is constituted by several stages. These steps range from consultation to specialists in order to define the indicators of sustainable development, to the graphic representation of the results. The classes that make up the index are critical, alert, moderate, acceptable, and ideal. The scale interval amplitudes are based on the Municipal Human Development Index (HDI-M), which is characterized as an index that uses a global methodology. In addition, a comparison was made between the proposed index and the Sustainability Barometer (BS).The results showed that no city in Ceará is in the best classification of the ES (ideal), while more than 50% of the places are inserted at the “critical” level.In addition, the performance of the state, in general, is set as "critical", and when comparing with BS, it was verified that the values found when applying the ES methodology are less conservative.